A Vibrational Spectroscopic Study of Transition Metal Tetracyanonickel Complexes of 2 Chloropyridine and 2 Bromopyridine - Bakiler, Meriç; Davies, J. Eric D.; AKYÜZ, SEVİM (Taylor and Francis Online, 1996)
The FT-IR and Raman spectra of eight new complexes of formula ML2Ni(CN)4 (where M = Mn, Fe, Co, Ni, Cu or Cd and L = 2-chloropyridine; M = Ni or Cd and L = 2-bromopyridine) are reported. The spectroscopic results indicate that the complexes have structures consisting of corrugated polymeric layers of [M-Ni(CN)4]∞ with 2-substituted pyridine molecules bound directly to the metal (M). For a given ligand (2-Clpy or 2-Brpy) the effects of metal-ligand bond formation on the ligand modes are examined. Metal-ligand bond strengths of the halo-derivatives of pyridine (L = 2-Clpy or 2-Brpy), inferred by the effects on frequency shifts of certain ligand modes, have also been compared.
Keywords: tetrocyanonickelate; vibrational spectroscopy; transition metal